Oxygen therapy target ranges: finding the balance. Issue 3 (30th September 2021) - Yu, Christiaan; Miller, Belinda R.
Ever since the Great Oxidation Event over 2 billion years ago, appropriate levels of oxygen have been essential for life on earth. Aerobic metabolism requires oxygen to produce energy in the mitochondria. Hypoxia refers to situations where there is lower than normal oxygen partial pressure in tissues and this may arise from hypoxaemia, or from impairments of oxygen delivery to tissues, of cellular uptake or of intra-cellular utilisation. Compensatory mechanisms exist in the pulmonary and systemic circulation, and different cell types have varying degrees of tolerance for limited periods of hypoxia, but failure or exhaustion of these adaptations can result in cell death [1]. Supplemental oxygen is routinely used to correct hypoxaemia, often guided by oxygen saturation targets. Inappropriate, absent or disregarded upper and lower limits can result in extended periods of hyperoxia or hypoxia. Clinical practice regarding oxygen therapy is changing, with increasing evidence that hyperoxia should be avoided. The lower oxygen target ranges need ongoing evaluation: a careful approach, including assessment of an individual's risks, is needed. https://bit.ly/3hNTgVv